Evaluation of aromatic rice cultivars in foot-hill zone of West Bengal - DE, D K; PAL, S K; GHOSH, M; PAL, A K; BASAK, S (The Indian Journal of Agricultural Sciences, 2014)
A field experiment ws conducted during the rainy season of 1999 and 2000 at food-hill zone of West Bengal, to study the performance of 14 aromatic rice (Oryza sativa L.) cultivars including a local check. In dwarf, medium-late duration group, 'Haryana Basmati','Karnal Local', 'PK 1505-9-2-13-1' having >2.0 tonnes/ha yield potentiality, higher nurtrient assimilating power from native and ferrtilizer sources,>75% brown rice recovery, loong-wlender type kernel and strong to moderate aroim might be adopted in this zone condisidering both domestic as well as export purposes. However, among tall, long- duration ones'Seetabhog' performed well by producing >200 filled grains/panicle>1.8 tonnes/ha grain yield,> 75% brown rice recovery, relatively higher nutrient assimilation efficiency and moderate aroma. This cultivar might therefore, be selected as promising among short-grained ones.